Ensuring the future of Atlantic bluefin tuna - B. A. Block; E. A. Aalto; C. M. L. S. Pagniello; R. E. Whitlock; M. J. W. Stokesbury; R. J. Schallert; M. R. Castleton; J. F. Walter; K. Ferter; L. Nøttestad; O. Bjelland; H. W. Maxwell; et al. (Proceedings of the National Academy of Sciences, 2026)
Atlantic bluefin tuna (ABT) are a highly migratory fish that have been exploited by fishers for more than two millennia. This lucrative fishery is managed by the International Commission for Conservation of Atlantic Tunas (ICCAT), formed by 55 contracting parties. Implementation by ICCAT of an ABT recovery plan and decades of conservation efforts have led to significant progress and the species is rebounding throughout its range. Here, we combine and report on three decades of ABT electronic tag data from five nations that provide fisheries-independent biological information and spatially explicit track data vital to understanding the species’ life history. Tag data, state-space modeling, and spawning ground assignments enable estimations of fisheries area utilization, population overlap, and natural mortality that improve the accuracy of management models. We also examine the distribution of ABT fisheries impact over 70 years by assessing ICCAT catch reporting by fleet, gear type, and region. We hypothesize that, under the historical two-stock management paradigm, escapement of eastern juveniles and subadults from the Mediterranean Sea to the lower fishing mortality of the North Atlantic has contributed to the recovery of the eastern stock, with the 45°W meridian acting as an indirect conservation measure for migrating ABT in the West Atlantic. Although recent Management Strategy Evaluation modeling in ICCAT partly incorporates this migration behavior into catch composition estimates and recognizes the contribution provided by eastern migrants to western Atlantic biomass, these complex trans-Atlantic migratory behaviors need to be accounted for in future stock assessments and management. Tag data and development of genomic technology for dockside catch origin assignments can support improvements of stock assessments that will ensure the sustainability of ABT.